0904 Effects Of An Internet-based Cbt-i Intervention On Sleep And Asthma Control In Adults With Co-occurring Insomnia And Asthma. (27th April 2018) - Luyster, F S; Ritterband, L; Sereika, S; Strollo, P
Abstract: Introduction: Insomnia symptoms are commonly reported among individuals with asthma and can negatively affect asthma control. Targeted treatments for insomnia could improve asthma control and reduce disease burden. The purpose of this pilot study was to test the feasibility of a behavioral Internet-based insomnia intervention and gather preliminary efficacy data on the extent of change in insomnia and asthma control in adults with not well-controlled asthma. Methods: A within subject, pre-post design was used. Of the 56 participants screened, 23 (41.1%) met the eligibility criteria. The Internet-based insomnia intervention, Sleep Healthy Using the Internet (SHUTi), delivers the primary components of cognitive-behavioral therapy for insomnia (CBT-I). The primary outcomes were Insomnia Severity Index (ISI), Asthma Control Test (ACT), and Marks Asthma Quality of Life (AQOL). Post-treatment qualitative interviews explored patients' preferences for asthma-related content within the SHUTi program. Results: Of the 23 participants enrolled, 19 (82.6%) completed post-treatment assessments and 4 dropped out (n=2, 8.7%) or were unable to be contacted after baseline but before initiation of SHUTi (n=2, 8.7%). Participants' average age was 42.4 years (SD=11.6); most were female (63%), Caucasian (47%), and had some college (47%). There were significant mean decrease in ISI scores (ΔISI=-5.9 ± 4.9, p<0.001) and increase in ACT scores (ΔACT=3.8 ± 4.6, p=0.02) and a trend towards a decrease in AQOL scores (ΔAQOL=-1.0 ± 2.0, p=0.05), indicating improvements in outcomes. These observed changes had corresponding medium to large effect sizes (ISI=-1.2, ACT=0.81, AQOL=-0.49). Most (79%) indicated that the SHUTi program was mostly or very easy to use; 68% described the intervention material as useful; 53% reported that the intervention was mostly or very effective. Participants expressed a need for information about the relationship between insomnia and asthma in the SHUTi program. Conclusion: Preliminary findings indicate that CBT-I delivered via the Internet is a feasible treatment option for asthmatics experiencing insomnia and can improve sleep and asthma control. Support (If Any): This project was supported by the National Institutes of Health through Grant Numbers R03HL135213 and UL1TR001857.